Kualitas Air dan Status Kesuburan Perairan Waduk Sempor, Kebumen - Fuquh Rahmat Shaleh; Kadarwan Soewardi; Sigid Hariyadi (Jurnal Ilmu Pertanian Indonesia, 2014)
Sempor Reservoir is one of the reservoir in Central Java. This reservoir has primary function as irrigation and hydropower source. Beside, it also has some benefit for fisheries and tourism activities. Reservoir utilization which has not been optimum yet need some adjustments with water quality and aquatic trophic state in Sempor Reservoir. This study was aimed to determine water quality and aquatic trophic state of Sempor Reservoir. This study was conducted from January to March 2014 with monthly water sampling. Survey method to collect data with stratified random sampling was used for four represented station. Aquatic trophic state determination was based in Carlson Trophic State Index (TSI) measurement. This method used some represented parameters of physics, chemistry and biology such as water transparency, total phosphorus, and chlorophyll-a. The results showed that water quality of Sempor Reservoir was still good for fishery activities. Aquatic trophic state of Sempor Reservoir based on Carlson TSI was classified to low-medium in euthropic category ranging from 50.71-64.91. Inlet was the only area which had medium category of eutrophic due to highly nutrient content derived from anthropogenic activities nearby.